“Why Can Other People Live Normally While I Cannot?”: An Application of Telecounseling Due to COVID-19 - Darmayanti, Kusumasari Kartika Hima; Winata, Efan Yudha; Anggraini, Erlina (UI Scholars Hub, 2020)
In Nusa Tenggara Barat province, on May 04, 2020, there were 275 cases out of 11,587 total cases in Indonesia. COVID19 not only has an impact on physical health issues, but it also impacts on psychological issues. One of the psychological issues is how society experiences negative emotion (e.g., depression) during the spread of COVID-19. This study aimed to explore the telecounseling process on the individual who had experienced negative emotion especially in the case of depressive disorder in the COVID-19 Nusa Tenggara Barat province. This study used a single-case research design approach, and the collected data were analyzed qualitatively. The results showed that the participant reported everything she felt and thought about in stage I. Next, in stage II, the participant analyzed what she thought and wished. The statements of having suicidal thoughts, having negative emotions (e.g., feeling sad) and not being interested in any activities indicated that the participant experienced severe depression (BDI-II). Stage III took the form of a strategy of how the participant realized her goals. Through the telecounseling process, the participant understood the goals and strategies to achieve them amid COVID-19.